Colloidal clusters as models for circular microswimmers - Bipul Biswas; Hima Nagamanasa Kandula (Communications Physics)
Abstract Circular swimmers, particles that propel in circular trajectories, are gaining traction due to their potential for novel collective behaviors. However, synthetic active particles capable of controlled circular propulsion remain scarce. We present a facile experimental strategy to fabricate synthetic swimmers using chemically cross-linked Janus colloid clusters, driven by induced charge electrophoresis. By quantifying the propulsion dynamics of active clusters, we demonstrate that cluster geometry dictates orbit diameter, angular velocity, and chirality. Through statistical analysis of clusters, we identify compact clusters as promising candidates for tunable circular propulsion. To scale up fabrication, we employ capillary-assisted assembly for achieving monodisperse clusters. Our validation of the kinetic model for active trimers and tetramers suggests that clustering as a strategy for circular propulsion extends to Janus colloids propelled by different mechanisms. Our findings establish Janus clusters as versatile systems for controlled circular propulsion, enabling new experimental studies on the collective behavior of circular microswimmers.